Temperature and material flow in one-step double-acting friction stir welding process of aluminum alloy: Modeling and experimental - Eko Prasetya Budiana; Sekar Gading Happy Hapsari; Essam R. I. Mahmoud; Triyono Triyono (Universitas Muhammadiyah Magelang, 2025)
Aluminum, known for its lower density compared to steel, is widely used in various applications. Welding is often required to form aluminum into technical structures. However, when fusion welding is used, it can lead to porosity in the weld. This occurs due to the significant difference in hydrogen gas solubility between liquid and solid aluminum, which traps hydrogen gas within the weld metal. Friction Stir Welding (FSW), a solid-state welding technique, has been proven to minimize porosity. However, for thick structures, FSW poses challenges, as welding must be done on both sides, increasing the welding time. To overcome this limitation, FSW has been modified into a one-step double-side FSW process, where two tools simultaneously work on both surfaces of the workpiece. This creates a unique condition with two heat sources and two stirring motion sources. To understand the temperature distribution and material flow in this process, modeling was conducted using Computational Fluid Dynamics (CFD). The upper and lower tools in the one-step double-side FSW process operate under identical conditions: a rotation speed of 1500 rpm, a welding speed of 30 mm/min, and a tilt angle of 0 degrees. The aluminum plate is treated as fluid, while the tools are considered solid in the model. The results of the temperature distribution modeling were validated against published studies, and the material flow was verified through macro- and microstructural observations of the cross-section. The validation showed that the model is accurate, with an error of only 4.07%.